A galectin from Eriocheir sinensis functions as pattern recognition receptor enhancing microbe agglutination and haemocytes encapsulation. (August 2016) - Wang, Mengqiang; Wang, Lingling; Huang, Mengmeng; Yi, Qilin; Guo, Ying; Gai, Yunchao; Wang, Hao; Zhang, Huan; Song, Linsheng
Abstract: Galectins are a family of β-galactoside binding lectins that function as pattern recognition receptors (PRRs) in innate immune system of both vertebrates and invertebrates. The cDNA of Chinese mitten crab Eriocheir sinensis galectin (designated as EsGal) was cloned via rapid amplification of cDNA ends (RACE) technique based on expressed sequence tags (ESTs) analysis. The full-length cDNA of EsGal was 999 bp. Its open reading frame encoded a polypeptide of 218 amino acids containing a GLECT/Gal-bind_lectin domain and a proline/glycine rich low complexity region. The deduced amino acid sequence and domain organization of EsGal were highly similar to those of crustacean galectins. The mRNA transcripts of EsGal were found to be constitutively expressed in a wide range of tissues and mainly in hepatopancreas, gill and haemocytes. The mRNA expression level of EsGal increased rapidly and significantly after crabs were stimulated by different microbes. The recombinant EsGal (rEsGal) could bind various pathogen-associated molecular patterns (PAMPs), including lipopolysaccharide (LPS), peptidoglycan (PGN) and glucan (GLU), and exhibited strong activity to agglutinate Escherichia coli, Vibrio anguillarum, Bacillus subtilis, Micrococcus luteus, Staphylococcus aureus and Pichia pastoris, and such agglutinating activity could be inhibited by bothd -galactose and α-lactose. The in vitro encapsulation assay revealed that rEsGal could enhance the encapsulation of haemocytes towards agarose beads. These results collectively suggested that EsGal played crucial roles in the immune recognition and elimination of pathogens and contributed to the innate immune response against various microbes in crabs. Highlights: A galectin is identified in Chinese mitten crab Eriocheir sinensis. Its mRNA transcripts were significantly induced after microbe stimulation. Recombinant Es Gal (r Es Gal) binds various pathogen-associated molecular patterns. The r Es Gal enhances microbe agglutination and haemocytes encapsulation.